Cynaroside ameliorates TNBS-induced colitis by inhibiting intestinal epithelial cell apoptosis via the PI3K/AKT signalling pathway - Huang, Ju; Li, Jing; Geng, Zhijun; Yin, Lixia; Niu, Minzhu; Li, Qingqing; Liu, Xinyue; Cheng, Xinke; Zhang, Xiaofeng; Song, Xue; Wang, Yueyue; Wang, Lian; et al. (Frontiers in Pharmacology, 2025)
Background and aimsPatients with Crohn’s disease (CD) exhibit excessive apoptosis of intestinal epithelial cells (IECs), which contributes to damage to the intestinal barrier structure and function, thereby playing a role in the progression of colitis. Preventing IEC apoptosis and protecting the intestinal barrier are critical to alleviating colitis. Natural plant monomers have been reported to possess multiple pharmacological properties, particularly with the potential to treat CD. This study focuses on Cynaroside (Cyn) to explore its effect on IEC apoptosis and evaluate its pharmacological impact on the intestinal barrier and colitis.MethodsThe 2,4,6-trinitrobenzenesulfonic acid (TNBS)-induced CD-like colitis mice model was employed in this study. We assessed the therapeutic effect of Cyn on CD-like colitis by evaluating the disease activity index (DAI), body weight changes, intestinal tissue pathological damage, and inflammatory factor levels. Immunofluorescence and Western blotting were used to detect the expression and localization of tight junction (TJ) proteins, allowing us to analyze the intestinal barrier structure. The function of the intestinal barrier was examined using FITC-dextran (FD4), TEER values, and bacterial translocation. Network pharmacology enrichment analysis revealed that Cyn could inhibit cell apoptosis. We also explored the effect and underlying mechanism of Cyn in inhibiting IEC apoptosis on intestinal barrier function and colitis using both the TNF-α-induced colonic organoid model and the TNBS-induced mouse model.ResultsOur findings show that Cyn significantly alleviates TNBS-induced colitis symptoms in mice, as evidenced by reduced body weight loss, colon shortening, DAI score, colon histopathology score, and lower levels of inflammatory factors (IL-1β, TNF-α, and IL-6) compared to the model group. Additionally, the Cyn intervention group showed significant improvements in both the intestinal barrier structure (elevated tight junction protein levels and proper localization) and function (reduced serum FD4 levels, increased intestinal TEER, and decreased bacterial translocation rates in mesenteric lymph nodes [MLNs] and livers). Combining network pharmacology prediction analysis with our validation data from animal models and colonic organoids, we demonstrated that Cyn significantly inhibits IEC apoptosis, as indicated by a decrease in the proportion of TUNEL-positive cells and changes in apoptosis-related protein levels. KEGG enrichment analysis and signaling pathway intervention experiments confirmed that Cyn inhibits the activation of PI3K/AKT signaling.ConclusionCyn inhibits IEC apoptosis by blocking the PI3K/AKT signaling pathway, which is the primary mechanism underlying its protective effects on the intestinal barrier and its ability to improve CD-like colitis. This study also supports the potential of the Chinese medicine monomer Cyn as a promising therapeutic agent for the treatment of CD.